Analysis of Self-Control, Income Stability, and Problem-Solving Skills on Budgeting Behavior - Abigaiel C. Lesbasa; Hwihanus (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
Migrant students often experience unstable financial conditions, face increasing living-cost pressures, and have limited experience in managing personal finances independently. These challenges require adequate financial adaptability to enable students to manage their expenditures effectively and maintain financial stability. This study aims to examine the effects of Self-Control, Income Stability, and Problem-Solving Skill on Budgeting Behavior, both directly and indirectly through the mediating role of Financial Adaptability and the moderating role of Cost of Living Level. A quantitative approach was employed involving 70 migrant students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that Self-Control and Problem-Solving Skill have positive and significant effects on Financial Adaptability, whereas Income Stability does not significantly affect Financial Adaptability. Furthermore, Budgeting Behavior is positively and significantly influenced by Income Stability and Financial Adaptability, while Self-Control, Problem-Solving Skill, and Cost of Living Level do not have significant direct effects on Budgeting Behavior. In addition, Financial Adaptability does not mediate the relationships between the three independent variables and Budgeting Behavior. Likewise, Cost of Living Level does not moderate the relationship between Financial Adaptability and Budgeting Behavior. These findings demonstrate that income stability and financial adaptability play a more substantial role in explaining migrant students’ budgeting behavior than the psychological factors examined in this study. The study highlights the importance of strengthening financial adaptability and maintaining income stability as key determinants of effective budgeting behavior among migrant students. Keywords: Self-Control, Income Stability, Problem-Solving Skill, Financial Adaptability, Budgeting Behavior.